Financial analysis of the business of the Belgrade Stock Exchange - Đaković Miloš; Inđić Milica; Cicmil Danica (Trendovi u Poslovanju)
Financial exchanges are the basic form of a country's financial market. The subject of this research is the Belgrade Stock Exchange, while the aim of the paper is to analyze the main indicators of the business of the stock exchange as a single company. The analysis covers the period from 2017 to 2020, where in addition to observing the basic items of assets, liabilities, income and expenses of the stock exchange, we also deal with the ratio analysis of liquidity, indebtedness, coverage, activities and profitability of the stock exchange. The results indicate a pronounced liquidity of the market and debt control, but very low profitability of the company itself. Financial analysis also provides additional more precise insight into the business of the stock exchange as a single company. The paper also provides a basis for further research in terms of comparative analysis with other developed stock exchanges in the world.